Research funding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Financing Agricultural Research: A Sourcebook. Edited by S R Tabor, W Janssen and H Bruneau. 1998. 362 pp. ISBN 92 9118 035 1 ISNAR PO Box 93375 2509 AJ The Hague The Netherlands. Fax: +31 70 381 9677 Email: isnar@cgnet.com http://www.agricta.o